Rome and Naples: differences and similarities between squatting experiences - Davoli, Chiara; De Falco, Ciro Clemente; Punziano, Gabriella (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
This article analyses continuities and discontinuities in the squatting experiences of two different Italian cases: Rome and Naples. The aim is to use these two main illustrative cases to discuss meanings, structures and principles that emerge from the two selected experiences. This because these are two different expressions of the squatting experience: on one side with a history of a long tradition, as it is in the case of Rome; on the other side with a history that only recently has known a process of consolidation, as it is in the case of Naples. The cases were approached from a comparative qualitative point of view since with this study we do not intend to frame the two experiences as final models. In fact, we want to explore the local aspects that enable us to understand the differences among housing struggles, coalitions, organisation of movements and, in general, social, urban and housing movements in Rome and Naples. For this reason the paper aims to contribute to the current debate by providing new insights and thought-provoking elements in the general study of the squatting phenomenon.